Ángeles de desolación / Jack Kerouac - Kerouac, Jack; Maria del Carmen Azpiazu (España, 1975)
Novela
Incluye: bibliografía, imagen, índice onomástico
Col. OGen
Keywords: 1. OBRA GENERAL 2. LITERATURA 2. NOVELA